PNEUMONIA IN CHILDREN: CAUSES AND MODERN OPPORTUNITIES OF PROPHYLAXIS - E.V. Galkina ("Paediatrician" Publishers LLC, 2011)
Out-of-hospital pneumonia is one of significant problems among infections of low airways in children. According to the data from international studies, the incidence of out-of-hospital pneumonia is 34-40 cases of 1,000 children per year. The prevalence of this disease in Russia is lower: different data show 4-12 cases of 1,000 children 1 month old-15 years old. Low prevalence is related to more rough criteria of pneumonia diagnostics. Out-of hospital pneumonia doesn't result in death frequently, but in developing countries it is the leading cause of children's mortality. Every year 700 thousands - 1 million children die because of pneumococcal infection. That's why the questions of timely diagnostics, adequate treatment and specific prophylaxis are topical. The literature review is performed for highlighting of questions of pneumonia development and diagnostics of patients with opportunity of efficient specific prophylaxis. Key words: children, pneumonia, immunodeficiency state, prophylaxis. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 23-28)